Pengaruh Kompensasi terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening pada PT XYZ Cabang Jambi - Heri Fitriansyah; Rohman Wilian; Feny Tialonawarmi (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study aims to determine the effect of compensation on employee performance through job satisfaction as an intervening variable at PT Sumber Alfaria Trijaya Tbk Jambi Branch. The population and sample in the study were all employees of PT Sumber Alfaria Trijaya Tbk Jambi Branch totaling 754 employees, while the sample was determined using a sampling method adjusted to the research needs of 89 employees. This study uses a quantitative approach and data were collected through a questionnaire method. The data analysis method of this study is descriptive statistical analysis using the Structural Equation Model (SEM) technique using the SmartPLS 4 program analysis tool. Model testing includes convergent validity testing through outer loading and Average Variance Extracted (AVE) values, discriminant validity testing, and reliability testing through Composite Reliability and Cronbach's Alpha values. Evaluation of the structural model was carried out by looking at the R-Square value, direct effect, indirect effect, and hypothesis testing through t-statistic and p-value. Based on the results of the study, it shows that the average employee performance score of 397.2 is included in the very high category; compensation of 394.3 is included in the very high category; and job satisfaction of 399.1, categorized as very high. The results of the PLS test indicate that compensation has a positive and significant effect on employee performance; compensation has a positive and significant effect on job satisfaction; job satisfaction has a positive and significant effect on employee performance; and compensation has a positive and significant effect on employee performance through job satisfaction as an intervening variable. This research recommends: (1) For the employee performance variable, companies are advised to provide time management training and conduct regular evaluations to achieve work targets more consistently. (2) For the compensation variable, companies need to improve the suitability and availability of work facilities to support effective task implementation. (3) For the job satisfaction variable, companies are advised to improve the work environment and enhance the quality of physical facilities to increase employee comfort and satisfaction.